EFEK MUSIK TERHADAP PERUBAHAN INTENSITAS NYERI PADA PASIEN POST OPERASI DI RUANG BEDAH RSUP Dr. SARDJITO YOGYAKARTA - Edi Purwanto (Saintika Medika, 2009)
During post operative period, treatment process aimed to stabilize patient physiology equilibrium and to eliminate the pain. Physiological reactions of the pain are autonomous nerve responds like speed of breathing, increase of the pulse, and expenditure of adrenalin. Music can decrease of patient pain, because it is the same nerve not only to feel the pain but also to listen to the music, so that at the same time when the patient feel the pain it might be distract by listen to the music. This research aim is to know the effect of music to pain intensity at post operative patient. This research method is pre-experiment design by using design group post-test and pre-test. Technique intake are using sampling quota with amount of sample are 30 respondents. Statistical test using paired sample t-test analyses method. Confidence interval 95 %( α = 0,05). According to statistical test of paired sample t-test were got that mean pain scale at pre-test is 6,5667 with deviation standard are equal to 1,1651. While mean pain scale at post-test is 4,3000 with deviation standard are equal to 2,1679. Level of t-value is 7,389 with a significant equal to 0,000. By using α = 0,05 and df = 29 were got value of t the tables are equal to 2,045. With the t-value bigger than t-value tables and probability value 0,000 smaller than α = 0,05 hence can be concluded that Ho refused, meaning effect of the music can degrade pain intensity at postoperative patient in surgical ward Dr. Sardjito Hospital of Yogyakarta. Music can give a meaningful contribution in giving nursing intervention at postoperative pain patient in surgical ward Dr. Sardjito Hospital of Yogyakarta. This music could comfort, calm, and be able to distract patient attention to their pain. Keyword: Intensity of Pain, Postoperative, Effect of The Music